2006
DOI: 10.1074/jbc.c600164200
|View full text |Cite
|
Sign up to set email alerts
|

Separating the Anti-apoptotic and Mitotic Roles of Survivin

Abstract: Survivin is a bifunctional protein that acts as a suppressor of apoptosis and has an essential role in mitosis. To date whether these two functions can be divorced has not been addressed. Here we show that the linker region between the BIR (baculovirus inhibitor of apoptosis repeat) domain of survivin and COOH-terminal ␣ helix may be the key to separating its roles. When overexpressed survivin is present in interphase cells and shuttles between the cytoplasm and nucleus. Here we identify a rev-like nuclear exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
143
3
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(156 citation statements)
references
References 21 publications
7
143
3
3
Order By: Relevance
“…Cells were seeded at 2 x 10 4 per well (24 well plate) in anti-biotic free media then transfected with 60 pmol of control or survivin specific siRNA (Ambion) using HyperFect (Qiagen), as described in. 2 Constructs were rendered resistant to RNAi-targetting by introduction of a silent mutation, G54C. 20,21 Immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were seeded at 2 x 10 4 per well (24 well plate) in anti-biotic free media then transfected with 60 pmol of control or survivin specific siRNA (Ambion) using HyperFect (Qiagen), as described in. 2 Constructs were rendered resistant to RNAi-targetting by introduction of a silent mutation, G54C. 20,21 Immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 Immunoblotting. Immunoblot analysis was performed as described in Colnaghi et al (2006). Antibodies used: anti-survivin (1:750, rabbit, Ab469, Abcam) and anti-tubulin (B512, 1:2000, Sigma).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…XPO1 plays an essential role in the function of survivin, as its cytoplasmic localization is required for antiapoptotic and tumor-promoting functions of survivin (27,28). Studies using mutants with export-deficient survivin showed that tumor cells were more sensitive to radiotherapy-induced apoptosis (28,31,32). On the basis of these studies, we hypothesize that blocking survivin nuclear export using XPO1 inhibitors could prevent radiation resistance.…”
Section: Introductionmentioning
confidence: 97%
“…It has been demonstrated that svv is a member of the chromosomal passenger complex (CPC) proteins and interacts with Aurora-B kinase, Borealin and inner centromere protein (INCENP) to play a significant role in cell division (Lens et al 2006;Ruchaud et al 2007). In addition, svv contains a Crm1-dependent nuclear export signal (NES), which is essential for the anti-apoptotic and regulatory role of svv during cell division and its correct localization (Stauber et al 2006;Habtemichael et al 2010;Knauer et al 2007a, b;Colnaghi et al 2006). This gene is highly expressed in cancers including neuroblastoma, gastric cancer, colorectal cancer, and bladder cancer (Adida et al 1998;Lu et al 1998;Kawasaki et al 1998;Swana et al 1999).…”
Section: Introductionmentioning
confidence: 99%